Differentiation of high-fructose corn syrup adulterated Kelulut honey using physicochemical, rheological, and antibacterial parameters - Mohamat, Rinee Najwa; Mohammad Noor, Nur Rabiatul Adawiah; Yusof, Yus Aniza; Sabri, Suriana; Zawawi, Norhasnida (MDPI, 2023)
Kelulut (stingless bee) honey (KH) possesses a wide range of benefits for human consumption and can exhibit medical effects. Due to its high value, this premium honey is often adulterated with different types of cheaper sugars, causing low nutrients and potential food safety threats in the final product. This study aims to determine the physicochemical, rheological, and antibacterial properties of sugar-based adulterated KH from the stingless bee species Heterotrigona itama. Adulterated samples were prepared using pure honey mixed with different concentrations of high fructose corn syrup (HFCS), i.e., 10%, 20%, 30%, 40%, and 50%. Water activity, colour, total soluble solids, pH, turbidity, viscosity, and antimicrobial activity of KH were determined. In addition, the primary sugar composition (fructose, glucose, and trehalulose) was determined by high-performance liquid chromatography with evaporative light-scattering detection (HPLC-ELSD). This study shows that the increasing percentage of HFCS addition in the KH samples significantly increases (p < 0.05) the total soluble solids, colour, pH, turbidity, viscosity, glucose, and fructose content; meanwhile, the water activity and trehalulose were reduced significantly (p < 0.05). Antimicrobial activity against S. aureus was reduced significantly (p = 0.006) by an increased percentage of HFCS compared to Control. Antimicrobial activity against P. aeruginosa was also found to be reduced significantly but showed non-significant effect from an increased percentage of HFCS in honey (p = 0.413). The bacterium S. aureus was more vulnerable to treatment with honey from both Control and adulterated groups compared to P. aeruginosa. In conclusion, HFCS-adulterated KH and authentic KH can be differentiated using all the parameters investigated. These data are vital for the governing bodies to ensure that KH sold in the markets is free from HFCS adulteration.